Valuation of Transactions Related to Intangibles from Transfer Pricing and VAT Perspective - Berdzuli,Davit (2020)
What are the intangibles and how transactions related to them should be evaluated from a direct and indirect tax perspective is one of the crucial questions of the modern tax systems and business operators. OECD provides a combination of methods and rules that can be applied for direct tax purposes. However, answers to these questions are not easy to find in the European Value Added Tax (VAT) system. The thesis addresses the legal challenges inherent in the application of tax rules to intangibles, both from transfer pricing (TP) and VAT perspective. It provides an analysis of the basic features of TP and European VAT, as well as how the intangibles concept is understood in their context. The study also seeks to examine the challenges that acquire in the process of applying evaluation techniques accepted by VAT Directive and the possibility of using TP methods for determining the taxable amount for VAT purposes. The analysis demonstrates that in the light of the legal character of VAT there is not much room for harmonization.